Validation and cultural adaptation of the Arabic versions of the Mini–Mental Status Examination – 2 and Mini-Cog test - Albanna M (Dove Medical Press, 2017)
Mohammad Albanna,1,* Arij Yehya,2,* Abdalla Khairi,1 Elnour Dafeeah,1 Abdelsalam Elhadi,3 Lamia Rezgui,4 Shahada Al Kahlout,4 Adil Yousif,5 Basim Uthman,6 Hassen Al-Amin2 1Psychiatry Department, Hamad Medical Corporation, 2Psychiatry Department, Weill Cornell Medicine – Qatar, 3Primary Health Care Corporation, 4Geriatrics Department, Rumailah Hospital, Hamad Medical Corporation, 5Department of Mathematics, Statistics and Physics, College of Arts and Sciences, Qatar University, 6Neurology Department, Weill Cornell Medicine – Qatar, Doha, Qatar *These authors contributed equally to this work Introduction: The elderly population is increasing around the world, and the prevalence of dementia increases with age. Hence, it is expected that the number of people with dementia will increase significantly in the coming years. The Mini–Mental Status Examination – 2 (MMSE-2) and Mini-Cog are widely used tests to screen for dementia. These scales have good reliability and validity and are easy to administer in clinical and research settings. Aim: The purpose of this study was to validate the Arabic versions of MMSE-2 and Mini-Cog. These scales were assessed against the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition, Text Revision (DSM-IV-TR) criteria for dementia, as the gold standard.Methods: The standard versions of the MMSE-2 and Mini-Cog were translated to Arabic following the back-translation method. Then, a trained rater administered these tests to 134 Arab elderly aged >60 years. A physician, blind to the results of these two tests, assessed the participants for vascular dementia or probable Alzheimer’s disease, based on the DSM-IV-TR criteria.Results: The sample included 67.2% Qataris. The mean age was 74.86 years (standard deviation =7.71), and 61.9% did not attend school. The mean of the adjusted scores of MMSE-2 based on age and education level was 19.60 (standard deviation =6.58). According to DSM-IV-TR, 17.2% of the participants had dementia. Sensitivity and specificity of the MMSE-2 and the Mini-Cog together were 71.4% and 61.6%, respectively, which were better than those of each test alone.Conclusion: Together, the Arabic versions of MMSE-2 and Mini-Cog are good screening tools for cognitive impairment in Arabs. Keywords: dementia, validation, MMSE-2, Mini-Cog, Arabic version